Small-caliber vascular grafts based on a piezoelectric nanocomposite elastomer: Mechanical properties and biocompatibility. (September 2019) - Cafarelli, Andrea; Losi, Paola; Salgarella, Alice Rita; Barsotti, Maria Chiara; Di Cioccio, Ilaria Bice; Foffa, Ilenia; Vannozzi, Lorenzo; Pingue, Pasqualantonio; Soldani, Giorgio; Ricotti, Leonardo
Abstract: The development of small-caliber grafts still represents a challenge in the field of vascular prostheses. Among other factors, the mechanical properties mismatch between natural vessels and artificial devices limits the efficacy of state-of-the-art materials. In this paper, a novel nanocomposite graft with an internal diameter of 6 mm is proposed. The device is obtained through spray deposition using a semi-interpenetrating polymeric network combining poly(ether)urethane and polydimethilsyloxane. The inclusion of BaTiO3 nanoparticles endows the scaffold with piezoelectric properties, which may be exploited in the future to trigger beneficial biological effects. Graft characterization demonstrated a good nanoparticle dispersion and an overall porosity that was not influenced by the presence of nanoparticles. Graft mechanical properties resembled (or even ameliorated) the ones of natural vessels: both doped and non-doped samples showed a Young's modulus of ∼700 kPa in the radial direction and ∼900 kPa in the longitudinal direction, an ultimate tensile strength of ∼1 MPa, a strain to failure of ∼700%, a suture retention force of ∼1.7 N and a flexural rigidity of ∼2.5 × 10 −5  N m 2 . The two grafts differed in terms of burst strength that resulted ∼800 kPa for the control non-doped samples and ∼1100 kPa for the doped ones. The graft doped with BaTiO3 nanoparticles showed a d33 coefficient of 1.91 pm/V, almost double than the non-doped control. The device resulted highly stable, with a mass loss smaller than 2% over 3 months and an excellent biocompatibility. Graphical abstract: Image 1 Highlights: Nanocomposite vascular graft based on an elastomer doped with barium titanate nanoparticles. The nanocomposite graft matches or outperforms the mechanical properties of natural blood vessels. The nano-doped scaffold shows a peak piezoelectric constant of ∼20 pm/V. The graft has high biostability: mass loss smaller than 2% over 6 months. The scaffold shows an excellent biocompatibility.